Evaluation of the cytogenetic and genotoxic effects of an abamectin-based pesticide on Allium cepa roots - Ili, Pinar; Sari, Fikret (Archives of Biological Sciences, 2024)
Paper description: Abamectin, with insecticidal, anthelmintic, and acaricidal activities, one of the most intensively used pesticides, has toxic effects on some non-target organisms, raising concerns regarding its safety. Toxicity of abamectin, the active ingredient of commercial pesticide formulation Alopec® EC, was investigated by cytogenetic and comet assays in Allium cepa root tips. Abamectin was found to be cytogenotoxic for cepa. To protect public health and the environment, abamectin should be carefully regulated, with particular attention given to its concentration, especially in agroecosystems. Abstract: Abamectin, a widely used pesticide with insecticidal, anthelmintic, and acaricidal properties, has raised safety concerns due to its toxic effects on certain non-target organisms. The toxicity of abamectin, the active ingredient in the commercial pesticide formulation Alopec® EC, was evaluated using cytogenetic and comet assays on Allium cepa root tips. Mitotic index (MI) and phase index (PI) values were used for cytotoxicity assessment. Chromosomal aberration (CA) frequencies in the dividing cells and comet data were used for genotoxicity assessment. The root growth test showed a significant concentration-based decline in root growth after abamectin exposure, with a median effective concentration (EC50) of 2.50 mg/L. Following 96-hour exposure to three concentrations of abamectin (1.25, 2.50, and 5.00 mg/L), cytogenetic and comet analyses indicated a significant concentration- and time-dependent decrease in the MI, alongside an increase in DNA damage. Additionally, there was a significant concentration-dependent rise in the total frequency of CAs. These findings show that abamectin is a pesticide with lethal effects on A. cepa root tip meristematic cells, even at lower concentrations, over prolonged exposure times, with CA-forming and DNA-damaging effects, and that it is highly cytotoxic and genotoxic.